2019
DOI: 10.3126/nvj.v36i0.27750
|View full text |Cite
|
Sign up to set email alerts
|

Study on Status of Fish Diseases in Nepal

Abstract: Fisheries play an important role in increasing the Nepalese economy as well as sustaining livelihood of some ethnic groups of our country. With the increased demand of fish, pisciculture have also increased to a great extend. Due to the rise in fish culture, there has been also rise in fish diseases. The study aims to investigate different parasitic, bacterial, fungal diseases in fish and to suggest treatment to control the diseases in four different fish farm of Nepal. A cross- sectional qualitative method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…1330341.6 per hectare). The B/C ratio of 1.63 found in fish farming in the Chitwan district [ 2 ] implies fish farming in the study area was more profitable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1330341.6 per hectare). The B/C ratio of 1.63 found in fish farming in the Chitwan district [ 2 ] implies fish farming in the study area was more profitable.…”
Section: Resultsmentioning
confidence: 99%
“…Nepal is a country with huge availability of water resources, so it has a great potential for fish farming [ 1 ]. In Nepal, 252 fish species are available in various aqua ecosystems, among them 236 are indigenous are and 16 exotic fish species [ 2 ]. There are 45,936 fish ponds in the country.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, some prior studies reported that formalin (150 ppm) was effective against gill rot (Shrestha et al, 2019). Similarly, it was reported that the combined efficacy of Ciphalexin (80 mg/Kg of feed) and Kohrsolin-TH (900 ml/ha) was 97.7 percent for controlling EUS infection in carp species (Rai et al, 2014).…”
Section: Fish Disease Managementmentioning
confidence: 94%
“…Approximately 232 of the 252 fish species in Nepal, many of which are tiny indigenous species (SIS), are the result of the finfish biodiversity (Shrestha et al, 2019). Numerous research support the claim that SIS normally provide communities around the country with substantially greater nutritional values (Pulkkinen et al, 2010).…”
Section: Aquaculture In Nepalmentioning
confidence: 99%
See 1 more Smart Citation